Comparison of some information criteria performance for selecting time series models in lower orders (المجلة العراقية للعلوم الاحصائية, 2011)
In this research we display some information criteria for time series like AIC,BIC,AICc and others. Beside that a proposal criteria is NAICc , two methods have been used for comparison of performance criteria by simulated and real data and we got encouraging results.